Measurements of diffusion, T1 and T2 in one shot by MMME - Ren, Xiaohong; Song, Yi-Qiao (Diffusion Fundamentals, 2009)
In this paper, we demonstrate a rapid simultaneous measurement of diffusion constant D, T1 and T2 relaxation times in just two scans. Theoretical standard deviations of D, T1 T2 for a wide range of T1 and T2 were predicted for given sequences with a random experimental error of 3%. By carefully selecting of sequence parameters for samples with different relaxation times, the error propagators in T1, T2, and D can be modified to within 10%.